Analysis of the Effectiveness of Physiotherapy Services in Homecare Services - Panggabean, Martua Jaya Panggabean; Felix Kasim; Ika Nursaputri (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: National health development in Indonesia aims to improve public health through the active participation of various national components. Despite progress, challenges such as health disparities between regions and epidemiological transitions remain. Homecare physiotherapy, which provides care at the patient's home, has become an important solution, especially during the COVID-19 pandemic, which restricted social mobility. Research Objective: This study aims to analyze the effectiveness of homecare physiotherapy services in the Jakarta, Bogor, Tangerang, and Bekasi areas, as well as to explore the factors influencing productivity, quality, efficiency, flexibility, and patient satisfaction with these services. Research Method: This research uses a qualitative approach with a phenomenological design. Data was collected through in-depth interviews, direct observation, and documentation from physiotherapists, patients, and service managers. Data analysis was conducted using Grounded Theory and Analytical Hierarchy Process methods to identify priority policies. Research Findings: Homecare physiotherapy services have been proven effective in improving patients' physical conditions. Patients reported improvements after therapy, although challenges related to punctuality and patient readiness remain. Physiotherapists' productivity is high, despite external obstacles such as traffic congestion. Conclusion: Homecare physiotherapy services are effective in improving patients' conditions, but improvements are needed in time management, punctuality of visits, and schedule flexibility to enhance patient satisfaction.